FAKTOR PENDORONG MORO ISLAMIC LIBERATION FRONT (MILF) UNTUK MENANDATANGANI FRAMEWORK AGREEMENT OF BANGSAMORO (FAB) DENGAN PEMERINTAH FILIPINA PADA TAHUN 2012 - Tandio, Yolanda; Fasisaka, Idin; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
ABSTRACT The Philippine government has had a prolonged conflict with armed group in Mindanao, South Philippines. One of the most influential groups in Mindanao is a MILF. MILF wants to establish an independent and sovereign state in the Southern Philippines as a result of the efforts of Christianization by the Philippine Government to cause land disputes and power shift. However, it has never been realized until giving rise to various rebellions. The various peace process has been done, such as the Tripoli Agreement, the Final Peace Agreement and the Memorandum of Agreement on Ancestral Domain but always failed. Finally succeeded with the signing of the Framework Agreement of Bangsamoro (FAB) in 2012 between the Philippine government and the MILF. FAB will contain the guarantee of basic rights Bangsmoro by the Government. This study shows that the motivating factor for MILF to sign FAB with the Philippine Government is a political recognition given to the Bangsamoro, special autonomy, as well as the creation of the Bangsamoro Basic Law that will include various things about the basic rights to the Bangsamoro. Keywords: Motivating factor, Political recognition